Теоретичні засади морального виховання у Великій Британії - Кучай Тетяна; Сулима Ольга; Дзямко Вікторія; Kuchai Tatiana; Sulym Olga; Dzуamko Viсtoria; Dzámko Viktória; Kucsáj Tetjána (РВВ ЦДПУ ім. В. Винниченка, 2020)
Резюме. У статті розглядаються теоретичні засади морального виховання у Великій Британії. Наголошено, на традиціях виховання моральних якостей в сучасній британській сім’ї. Провідним фактором виховання є моральний клімат сім’ї. Велика Британія відома як країна з міцними традиціями сімейного життя, де турбота про молоде покоління та виховання в нього моральних якостей посідає пріоритетне місце. Британські педагоги вважають, що опора на духовні цінності й ідеали, закладені в релігійних постулатах, сприяє моральному вихованню молодої людини, для якої загальноприйняті норми і принципи набувають особистої значущості.

Abstract. The article discusses the theoretical foundations of moral education in the Great Britain. Emphasis is placed on the traditions of the upbringing of moral qualities in the modern British family. A leading factor in nurturing is the moral climate of the family. The Great Britain is known as a country with strong traditions of family life, where caring for the younger generation and nurturing its moral qualities is a priority. British educators believe that the reliance on spiritual values and ideals embodied in religious tenets promotes the moral upbringing of a young person for whom generally accepted norms and principles are of personal importance. In the context of the global crisis of modern civilization in the Great Britain intensive search for other ways of education of the human personality is being conducted, the problems and prospects of family and school rapprochement within the modernization of the moral education and training system are clearly outlined. The task of Great Britain educators is to humanize the learning process. British society is extremely concerned about the widespread increase in spirituality, cruelty, and violence. It is the result of the influence of many factors of social, cultural, psychological order. Traditional basic moral concepts of good and evil English students learn in the family. Significant contributions to moral education are made by churches of different denominations, which largely form the basic moral qualities produced by mankind. The transformation of the family and the weakening of its educational functions, the decline of church authority among young people, as well as the significant problems of school education, authoritarian pedagogical traditions, encourage English educators to find more effective ways of moral education of students. British society is concerned about the many problems associated with family, which has traditionally been considered a starting point in the formation of moral ideas in children. The British are aware that in order to solve the problems of the family it is necessary to integrate all state and social forces, since the family must give the child the basic foundations of family life, and ensure its preparation for it. In the Great Britain, all participants in the educational process, especially parents, teachers, the community, have recognized the need for close mutual cooperation. This attitude to the problem leads to the conclusion that in the Great Britain moral education is a matter of national importance. Responsibility for the implementation of the process of moral education of children is shared between school and family.
Theoretical fundamentals of moral education in the Great Britain
http://eprints.mdpu.org.ua/id/eprint/10425/
Keywords: моральне виховання; Велика Британія; британська сім’я; традиції